CD56-Negative Aggressive NK Cell Leukemia Relapsing as Multiple Cranial Nerve Palsies: Case Report and Literature Review - Guerreiro, M.; Príncipe, F.; Teles, M. J.; Fonseca, S.; Santos, A. H.; Fonseca, E.; Gomes, P.; Marques, C.; Lima, M. (Case Reports in Hematology, 2017)
Background. Aggressive natural killer cell leukemia (ANKL) is extremely rare and habitually manifests as a systemic disease with multiorgan failure that rapidly evolves to death. The neoplastic natural killer (NK) cells usually harbor the Epstein-Barr virus (EBV) with a latent viral infection pattern type II; they often have a cytoplasmic CD3ε+ and surface CD3−, CD2+, and CD56+ immunophenotype, and they show complex genetic abnormalities affecting multiple tumor suppressor genes and oncogenes. We present a rare case of CD56-negative ANKL and review the clinical and laboratorial criteria for the diagnosis, as well as the available therapies. Case Presentation. A European 36-year-old male presented with acute onset fever, pallor, weakness, and jaundice. He had hepatosplenomegaly, severe pancytopenia, hepatic cytolysis, and very high serum lactic dehydrogenase levels. The bone marrow studies resulted in the diagnosis of an EBV-positive, CD56-negative ANKL. The patient failed to respond to gemcitabine and cisplatin-based polychemotherapy, dying three months later with leukemic meningitis and multiple cranial nerves palsies. Conclusions. The diagnosis of ANKL is difficult and requires both clinical suspicion and an extensive laboratorial approach. Absence of CD56 expression on the neoplastic NK cells may impose difficulties in the diagnosis, which requires morphological, immunophenotypic, histopathological, immunohistochemical, cytogenetic, and molecular studies.